2020
DOI: 10.1016/j.molmet.2020.101057
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics of human islet ontogeny defines the molecular basis of β-cell dedifferentiation in T2D

Abstract: Objective Dedifferentiation of pancreatic β-cells may reduce islet function in type 2 diabetes (T2D). However, the prevalence, plasticity and functional consequences of this cellular state remain unknown. Methods We employed single-cell RNAseq to detail the maturation program of α- and β-cells during human ontogeny. We also compared islets from non-diabetic and T2D individuals. Results Both α- and β-cells mature in part by repressing non-endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 90 publications
4
87
1
Order By: Relevance
“…The top 20 clusters are displayed and a stringent cut-off of 1e-6 was applied to determine significant gene ontology pathways. For gene-set-enrichment-analysis (GSEA) analysis, GSEA Preranked (4.0.1) ( 53 ) was run on a pre-ranked gene list using either user-provided pancreatic gene expression sets ( 22, 28 ) or standard hallmark gene signatures provided by the Molecular Signatures Database (MSigDB) ( 54 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The top 20 clusters are displayed and a stringent cut-off of 1e-6 was applied to determine significant gene ontology pathways. For gene-set-enrichment-analysis (GSEA) analysis, GSEA Preranked (4.0.1) ( 53 ) was run on a pre-ranked gene list using either user-provided pancreatic gene expression sets ( 22, 28 ) or standard hallmark gene signatures provided by the Molecular Signatures Database (MSigDB) ( 54 ).…”
Section: Methodsmentioning
confidence: 99%
“…S4b). We found that approximately 1.3% of cells from each individual donor (median across all donors) were classified as Hybrid cells, with the exception of one ABB+ donor (AAB+ #3), which was overrepresented in the Hybrid cluster ( Fig To gain further insight into the molecular nature of Hybrid cells, we next compared each Hybrid subpopulation to relevant canonical cell populations to determine their transcriptional divergence (tables S51 to 57) and convergence with respect to gene signatures of common pancreatic cell types (22,28). To this end, we observed the enrichment of the alpha cell signature in Endocrine-like Hybrids, the ductal cell signature in Ductal-like Hybrids, and the acinar cell signature in Acinar-like Hybrids.…”
Section: Single-cell Rna-seq Profiling Identifies Non-canonical Rarementioning
confidence: 99%
See 2 more Smart Citations
“…To validate our unbiased clustering results, we directly examined the expression of a broad list of published markers of mature β cell identity (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), "β cell disallowed" genes (30-32), markers of immature β cells and non-insulin-expressing β cell precursors (6,8,9,20,(33)(34)(35)(36), and islet hormones ( Figure 4). Several markers of immature β cells and β cell progenitor genes (MafB, Nnat, Sox17, Fev, and Myc), as well as most "β cells disallowed" genes (Ldha, Hk1, Mylk, Igfbp4, Ndrg2, Pcolce, and Slc16a2) showed down-regulation during normal β cell maturation but were not re-expressed in either type of diabetes.…”
Section: Gene-specific Expression Changes In β Cell Maturation and Dementioning
confidence: 99%